2020
DOI: 10.35542/osf.io/jncwt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Academic performance of K-12 students in an online-learning environment for mathematics increased during the shutdown of schools in wake of the Covid-19 pandemic

Abstract: The shutdown of schools in response to the rapid spread of COVID-19 poses risks to the education of young children, including a widening education gap. In the present article, we investigate how school closures in 2020 influenced the performance of German students in a curriculum-based online learning software for mathematics. We analyzed data from more than 30,000 K-12 students who computed over 800,000 mathematical problem sets before and during the shutdown, and found that students’ performance increased du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…This indicates that most remote learning measures implemented during the first school closures in spring 2020 were not effective for student learning; there was no difference between them and the absence of systematic teaching during summer vacation. Taking a closer look at studies that reported positive effects of school closures on student achievement, three of these studies (Meeter, 2021;Spitzer & Musslick, 2020;van der Velde et al, 2021) used some kind of online learning software to assess student achievement. Students in the studies of both Meeter (2021) and Spitzer and Musslick (2020) worked with online learning software for mathematics, and students in the study of van der Velde et al (2021) worked on online learning software for language learning (i.e., for French).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that most remote learning measures implemented during the first school closures in spring 2020 were not effective for student learning; there was no difference between them and the absence of systematic teaching during summer vacation. Taking a closer look at studies that reported positive effects of school closures on student achievement, three of these studies (Meeter, 2021;Spitzer & Musslick, 2020;van der Velde et al, 2021) used some kind of online learning software to assess student achievement. Students in the studies of both Meeter (2021) and Spitzer and Musslick (2020) worked with online learning software for mathematics, and students in the study of van der Velde et al (2021) worked on online learning software for language learning (i.e., for French).…”
Section: Discussionmentioning
confidence: 99%
“…Taking a closer look at studies that reported positive effects of school closures on student achievement, three of these studies (Meeter, 2021;Spitzer & Musslick, 2020;van der Velde et al, 2021) used some kind of online learning software to assess student achievement. Students in the studies of both Meeter (2021) and Spitzer and Musslick (2020) worked with online learning software for mathematics, and students in the study of van der Velde et al (2021) worked on online learning software for language learning (i.e., for French). Hence, the positive effects of COVID-19-related school closures on performance in such online learning programs may have occurred due to the increased use of software during school closures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formative online assessment seems to be a promising tool to engage students while schools are closed. Empirical studies of formative assessments during the first COVID-19 wave showed a performance increase compared to the regular classes in previous years (Meeter, 2021; for older students see Spitzer & Musslick, 2020). Still, the exact causal links remain unclear, because the samples were self-selected and the interventions were at the same time the competence assessment used as outcome (which facilitates method effects).…”
Section: Implications For Teachingmentioning
confidence: 99%